PERAN KOPERASI SUSU DAN PENGARUHNYA TERHADAP EFISIENSI PRODUKSI USAHATERNAK SAPI PERAH - Leo Rio Ependi Malau (Jurnal Agrisep, 2021)
National milk production has not been able to meet domestic demands. One way to increase national milk production is the development milk cooperatives. This study aimed (1) to measure the technical, allocative, and economic efficiency of dairy farm business and (2) to analyze the effect of cooperative roles and member participation on the production efficiency of dairy farm business. This research was conducted at KPSBU Lembang, West Java, with 95 farmers as respondents. Data were analyzed using scoring techniques, Data Envelopment Analysis (DEA), and Tobit regression. This study discovered that the average level of technical efficiency in dairy farming is high that increasing milk production should be directed at increasing business scale. It aligns with the CRS TE value, which is more dominantly influenced by SE than VRS TE. However, the allocative and economic efficiency is still low because the farmers have not allocated production inputs with minimal costs. Cooperative roles has a positive effect on technical and economic efficiency. Member participation has a positive effect on technical, allocative, and economic efficiency. These results strengthen that milk cooperatives' empowerment can be one solution to increasing national milk production by optimizing cooperatives' roles and increasing member participation quality